Nurses Awareness Regarding Detection of Tuberculosis Cases in Babylon Hospitals - Hayder Mohammed (Journal of Global Pharma Technology, 2018)
Tuberculosis consider one problem that threaten a public health in world and specially in developing countries, the detection of TB cases is very important in eliminate the prevalence rate of this disease among society and also lead to success the treatment regime of TB. The nursing staff has crucial role in given the appropriate care for patients and also direct contact with patients in various sites of health facilities, therefore the improve the nurses awareness regarding detection of TB cases is important to control and decrease the risk of spread this disease. Quantitative research, descriptive design cross sectional study consisting of 80 nurses working in different site at Al-Hilla General Teaching Hospital. The result show the number of male (52.5%) higher than the number of female (47.5%), more nurses with secondary certificate as educational level (44.0%), the assessment of response rate of study sample for knowledge and awareness related TB is moderate level (40.0%) as higher percentage while the attitude and practice related TB is equal assessment between low and moderate level (47.5%). Keywords: Nurses, Awareness, Detection of Tuberculosis, Babylon Hospitals.